Feasibility of production of pepper (Piper nigrum) in La Virgen de Sarapiquí, Heredia, Costa Rica - Monge-Cordero, Dennis (2013)
The aim of this study was to conduct a feasibility study for the pepper cultivation (Piper nigrum) in La Virgen de Sarapiquí, Costa Rica. During the months of March to June 2012, studies were conducted to determine commercial, technical and financial viability for the cultivation and production of 2.5 ha of pepper in La Virgen de Sarapiquí, Heredia, Costa Rica. The technical study shows that the selected location is suitable for this type of activity; as for financial viability, it is concluded that the project is feasible, this is determined by the resulting NPV of ¢15,531,127 and IRR of 19,4%.